(n+3)-Cyclization for the Formation of Benzo[7]annulene Derivatives via a [1,4]-Hydride Shift: A Novel Cyclization Mode Involving an Internal Redox Reaction - Nagaki, Jun; Kawasaki-Takasuka, Tomoko; Mori, Keiji (Synlett, 2024)
We report a unique synthetic route to benzo[7]annulene derivatives. When benzylidene malonates having a 1-(N,N-dialkylamino)alkyl group at the ortho-position are treated with a stoichiometric amount of M(OTf)3 (M = Sc, Yb, Gd), three transformations ([1,4]-hydride shift/isomerization into an enamine/intramolecular Stork enamine acylation) proceed sequentially to afford various benzo[7]annulene derivatives in moderate chemical yields. To our knowledge, the present reaction is the first example of an internal redox reaction involving a [1,n]-hydride shift/(n+3)-cyclization process.
Keywords: C–H bond functionalization; redox process; carbocycles; hydride shift; (n+3)-cyclization; benzo[7]annulene